Monitoring And Evaluation Of Adverse Drug Reaction In Emergency Medicine Department - Patel, Shreya; Patel, Sanskruti; Patel, Kinal; Patel, Krima (International Journal of Medical Research and Review, 2023)
Background: Any deviation from the intended beneficial effect of a medication results in a drug related problem. Adverse drug reactions (ADRs) are negative consequences of drug therapy. It is the fourth to sixth leading cause of mortality in the United States of America. Aims: To find out the proportion of medical emergency admissions that are secondary to Adverse Drug Reactions(ADRs). Settings and Designs: An observational, prospective study conducted at the Emergency Medicine Department, at Tertiary Care Teaching Hospital for 12 months, daily from 9 am to 5pm. Materials and Methods: Patients aged ≥ 18, who have given a written informed consent were included and patients not able to give willing consent and women presented with pregnancy were excluded in the study. The data was recorded in the case record form, The causality assessment was performed using WHO causality assessment scale. To determine the ADR severity, Modified Hartwig and Siegel scale was used. Statistical Analysis: The statistical evaluation was done with the help of Statistical Package for Social Science (SPSS) version 21.0 manufactured by IBM (demo version) and Microsoft Excel 2016. p< 0.05 was considered as statistically significant. Results: Elderly patients were having higher incidence of ADRs. Among all drug groups, the highest incidence were antimicrobials and drugs acting on blood. Majority patients either recovered or were in a recovering phase. Most of the ADRs were not preventable. Conclusions: Reporting of ADRs in a systematic way allows appropriate analysis and intervention which will improve the patient’s safety. Many ADRs could be preventable by avoiding certain drug/drug combinations, hospitalization, dose dependent side effects, appropriate individual dosing and applying the Antimicrobial Stewardship Programme. Keywords: Adverse Drug Reactions(ADRs), Antimicrobials, Emergency Medicine Department